ODS of dibenzothiopene with titanium-modified SBA-16. - Rivoira , Lorena Paola; Vallés , Verónica Alejandra; Beltramone , Andrea Raquel; Martínez , María Laura; Ledesma , Brenda Cecilia; Anunziata , Oscar Alfredo; Anunziata , Oscar Alfredo; Ledesma , Brenda Cecilia; Martínez , María Laura; Vallés , Verónica Alejandra (Universidad Tecnológica Nacional., 2015)
Over the past, oxidative desulfurization (ODS) has drawn considerable interest as a new alter native method for deep sulfur elimination from light oils. This can be attributed to its attrac tive properties, including lower temperature and pressure conditions and lower operating cost [1-3] than conventional hydrodesulfurization (HDS) process. Oxidation of organosulfur com pounds results in the formation of sulfoxides/sulfones, highly polar and hence easily removed by both extraction into polar solvents or by adsorption. Due to their low reactivity, diben zothiophene derivatives (DBTs) are the most refractory species to be eliminated from oils. Hence, the ODS process through which DBTs are converted to their corresponding sulfones involves great interest at present [4-6]. We recently reported a good performance of this sup port in hydrotreating processes [7]. In this work, we describe the preparation and characteriza tion of new mesoporous catalytic materials based on Ti-containing SBA-16. We study here, the effect of the preparation method of titania-modified SBA-16 (characteristics of the active Ti and/or TiO2 species) and the effect of the different operation conditions in ODS of DBT under mild conditions in order to find the best performance. TiO2-modified mesoporous SBA 16 and titanium-substituted mesoporous SBA-16 were developed and tested in the oxidative desulfurization (ODS) of dibenzothiophene prevailing in liquid fuel. We assessed the impact exerted on performance of different reaction variables, including (nature and amount of the active catalytic species, phase system, molar ratio of oxidant H2O2 and DBT, reaction tempe rature, nature of the substrate and reuse of catalysts).
Keywords: Ti-SBA-16; Anatase/SBA-16; ODS; DBT; Three phase system